Biogeography and relationships within the Melanthera alliance: A pantropical lineage (Compositae: Heliantheae: Ecliptinae). Issue 3 (4th June 2018) - Edwards, Robert D.; Cantley, Jason T.; Chau, Marian M.; Keeley, Sterling C.; Funk, Vicki A.
Abstract: The taxonomic history of the Melanthera alliance is long and convoluted with many generic name changes and requires a robust phylogeny to clarify taxonomic concepts within the group and to begin asking questions of its evolutionary history. For a time, prevailing classifications placed all species in the genus Melanthera except for a handful of tetraploids from the Hawaiian Islands being recognized as a distinct genus: Lipochaeta. Recent morphological revision has reopened debate by proposing six genera: Apowollastonia, Echinocephalum, Lipotriche, and Melanthera, and two Pacific Island genera representing diploids (Wollastonia) and tetraploids (Lipochaeta), plus four closely related genera expected to fall outside the alliance (Acunniana, Indocypraea, Lipoblepharis, Quadribractea). Here, we present the most comprehensive molecular phylogeny to date of the taxa variously associated with Melanthera in order to test these competing generic limits and explore the biogeographic history of this pantropical lineage. The data are consistent with six segregate genera, including the sinking of Hawaiian Islands members of Wollastonia (Melanthera) back into a broader concept of Lipochaeta, although there is currently no recognized morphological synapomorphy to distinguish Lipochaeta s.l. from Wollastonia. Our results suggest that the Melanthera alliance originated some time during the Pliocene or Pleistocene and a strong contemporary presence of the alliance and closely related Ecliptinae outgroups in the Americas suggests that this region may have been the center of origin with subsequent dispersal. We illustrate the difficulty of reconstructing the dispersal history of the remaining genera and present the most parsimonious colonization hypotheses.